A simple method of the detection of pork spoilage caused by Rahnella aquatilis. (October 2017) - Godziszewska, Jolanta; Guzek, Dominika; Pogorzelska, Ewelina; Brodowska, Marta; Górska-Horczyczak, Elżbieta; Sakowska, Anna; Wojtasik-Kalinowska, Iwona; Gantner, Magdalena; Wierzbicka, Agnieszka
Abstract: This paper describes a simple method focused on detection of roasted pork patties prepared from meat that was spoiled mainly by Rahnella aquatilis . The method includes application of PCR with species-specific primers differentiating R. aquatilis from other meat-spoiling Enterobacteriaceae and an electronic nose (E-nose) based on ultra-fast gas chromatography (UFGC). The volatile compound profile of R. aquatilis after heat treatment was described and compared to the volatile compound profile of minced pork patties that were stored up to 8 days. The results demonstrated that decreased relative content of trimethylamine and propanal in addition to the presence of benzeneacetaldehyde in odour of patties was linked to R. aquatilis – induced product spoilage. Highlights: E-nose and species-specific PCR were used for rapid detection of patties prepared from pork spoiled by Rahnella aquatilis. The species specific volatile compound profile of R. aquatilis after heat treatment was developed. Three indicators of pork changed by R. aquatilis were discovered.